Fatigue in incident peritoneal dialysis and mortality: A real-world side-by-side study in Brazil and the United States - Guedes, Murilo; Wallim, Liz; Guetter, Camila R.; Jiao, Yue; Rigodon, Vladimir; Mysayphonh, Chance; Usvyat, Len A.; Barretti, Pasqual; Kotanko, Peter; Larkin, John W.; Maddux, Franklin W.; Pecoits-Filho, Roberto; et al. (Public Library of Science (PLoS), 2022)
Background We tested if fatigue in incident Peritoneal Dialysis associated with an increased risk for mortality, independently from main confounders. Methods We conducted a side-by-side study from two of incident PD patients in Brazil and the United States. We used the same code to independently analyze data in both countries during 2004 to 2011. We included data from adults who completed KDQOL-SF vitality subscale within 90 days after starting PD. Vitality score was categorized in four groups: >50 (high vitality), ≥40 to ≤50 (moderate vitality), >35 to <40 (moderate fatigue), ≤35 (high fatigue; reference group). In each country’s cohort, we built four distinct models to estimate the associations between vitality (exposure) and all-cause mortality (outcome): (i) Cox regression model; (ii) competing risk model accounting for technique failure events; (iii) multilevel survival model of clinic-level clusters; (iv) multivariate regression model with smoothing splines treating vitality as a continuous measure. Analyses were adjusted for age, comorbidities, PD modality, hemoglobin, and albumin. A mixed-effects meta-analysis was used to pool hazard ratios (HRs) from both cohorts to model mortality risk for each 10-unit increase in vitality. Results We used data from 4,285 PD patients (Brazil n = 1,388 and United States n = 2,897). Model estimates showed lower vitality levels within 90 days of starting PD were associated with a higher risk of mortality, which was consistent in Brazil and the United States cohorts. In the multivariate survival model, each 10-unit increase in vitality score was associated with lower risk of all-cause mortality in both cohorts (Brazil HR = 0.79 [95%CI 0.70 to 0.90] and United States HR = 0.90 [95%CI 0.88 to 0.93], pooled HR = 0.86 [95%CI 0.75 to 0.98]). Results for all models provided consistent effect estimates. Conclusions Among patients in Brazil and the United States, lower vitality score in the initial months of PD was independently associated with all-cause mortality.